On the history of paper of Vilnius Gospel (without signatures) of 1600 from Mamonichs Publishing House - Bondar N. (Рукописна та книжкова спадщина України, 2014)

(untitled)
In the article watermarks of Gospel of 1600 without signatures from Vilnius Publishing House of Mamonichs are explored. As an example six copies from V. Vernadsky National Library of Ukraine holdings were chosen. The research enables us to determine the quantity of watermarks kinds and their percentage in circulation, to explore the dynamic of watermarks replacement and to define their origin. We have defined that more than half of paper used in the edition is produced in Lithuania but there also is a large amount of foreign paper, mostly of Cracow origin. The study also covers watermarks from two fragments of this edition, as well as those from copies held in the Library of Vilnius University and the National Library of Belarus. The kinds of filigrees at these copies differ from the filigrees at Kyiv copies. It was suggested that paper of different quality was purchased and more and less qualitative copies were batched for trading.